Norwegian-Japanese whaling relations in the early 20th century : a case of successful technology transfer - Mageli, Eldrid (Scandinavian Journal of History, 2006)
Publisher: Routledge
Keywords: Japan; Norge; Sørishavet; hvalindustri; pelagisk hvalfangst

Whaling or Shipping? Conflicts over the Use of the Norwegian Whaling Fleet during World War II - Basberg, Bjørn Lorens (International Journal of Maritime History, 1991)
When the United Kingdom entered World War n in September 1939 the Norwegian merchant marine was immediately affected, as its ships became the targets of German submarines. Between September 1939 and April 1940 (when Norway was occupied by the Nazis), more than fifty Norwegian ships were lost, mainly in the North Sea and the north Atlantic. In November 1939 an agreement was reached between the British government and the Norwegian Shipowners Association to place almost half the Norwegian merchant fleet at Britain's disposal under the so-called "charter parties scheme." The king and the Norwegian government fled to London and established a government-inexile during the German occupation, but before their departure it was decided to establish an agency in the British capital to operate and manage Norwegian shipping. It was named the Norwegian Shipping and Trade Mission (Nortraship) and became the world's largest shipowner, controlling more than one thousand ships at the outset of the war.'
Publisher: SAGE Publications Ltd
Keywords: Norge; Sørishavet; andre verdenskrig; hvalbåter; hvalfangstindustri; hvalindustri; pelagisk hvalfangst

Teori om internasjonale forhandlinger: Forhandlingene 1958-59 om kvoteregulering av hvalfangsten i Antarktis - Midgaard, Knut (Internasjonal politikk, 1974)
Keywords: Norge; Sørishavet; hvalfangstkvoter; internasjonal politikk; pelagisk hvalfangst